2022
DOI: 10.1177/10776990211066510
|View full text |Cite
|
Sign up to set email alerts
|

News Sources and Framing of Responsibility on Devolution in Kenya, 2013–2017

Abstract: The present research examines two aspects of newspaper coverage of devolution during a 4-year period between March 27, 2013, and May 28, 2017: first, through the lens of attribution of responsibility, who the news media most blamed for problems facing devolution; second, whether reliance on official sources in reporting of devolution mirrors the indexing hypothesis. Findings show that the most-blamed actor and dominant news source on devolution is the county executive. Journalists continue to rely on the elite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Consequently, the incessant disagreements between the Senate and the Executive over devolution affairs received wide media coverage (see Anami & Namuliro, 2013; Ontomwa, 2013)—knowing that conflict is a news value highly prevalent in journalistic practices. In fact, conflict was the most dominant media frame (40.2%) in the coverage of devolution during the same period under investigation (see Ochieng, 2019). This reflects Bennett et al’s (2006) argument that the press corps has a calibration process based on official consensus and conflict that determines “what gets into the news, what prominence it receives, how long it gets covered, and who gets the voice in these stories” (p. 49).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, the incessant disagreements between the Senate and the Executive over devolution affairs received wide media coverage (see Anami & Namuliro, 2013; Ontomwa, 2013)—knowing that conflict is a news value highly prevalent in journalistic practices. In fact, conflict was the most dominant media frame (40.2%) in the coverage of devolution during the same period under investigation (see Ochieng, 2019). This reflects Bennett et al’s (2006) argument that the press corps has a calibration process based on official consensus and conflict that determines “what gets into the news, what prominence it receives, how long it gets covered, and who gets the voice in these stories” (p. 49).…”
Section: Discussionmentioning
confidence: 97%
“…Today, whether on radio, television or newspapers, it’s rare to come across news coverage without reporting activities of a particular governor. For example, the four newspapers analyzed in this research have pages dedicated to news from counties, where Ochieng (2019) reported that county executives headed by governors were the main sources of devolution news (41.2%) in the same period under study—while national parliament (where senators are members) came third (13.1%) after the county assemblies (16.8%).…”
Section: Discussionmentioning
confidence: 99%